Conjuguer l’histoire : conjoncture et prospective - Morel, Bernard (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
Futurology often looks like a new undertaking, the object of which would be to give people "the fantastic and marvellous" that every one needs: make one dream of tomorrow. But if the future is an alibi, it must also be a tool for mobilization. Prospective gives then to itself a less emphatic purpose: it is a new way of reading past and present (that is to say to understand history) as to define the prospects which make the future. The future is not determined in a mecanic way. It is the resultant and the expression of different projects (projects of economical groups and classes), which meet, clash inside a complex economic and social formation.In another way, to read history goes with the idea the future is to be made, which only results of classes, struggle, social and international power-relations.The method must unite on one side a way of production trends analysis (abstract time), and a social formation evolution (concrete time). It is a way of thinking which obviously can use traditional technics.